If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(m + -3) + 6 = 61 Reorder the terms: 4(-3 + m) + 6 = 61 (-3 * 4 + m * 4) + 6 = 61 (-12 + 4m) + 6 = 61 Reorder the terms: -12 + 6 + 4m = 61 Combine like terms: -12 + 6 = -6 -6 + 4m = 61 Solving -6 + 4m = 61 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 4m = 61 + 6 Combine like terms: -6 + 6 = 0 0 + 4m = 61 + 6 4m = 61 + 6 Combine like terms: 61 + 6 = 67 4m = 67 Divide each side by '4'. m = 16.75 Simplifying m = 16.75
| 8.5+c=6 | | f(x)=3sin(x+3) | | 5x-4=7x-6 | | y=15+32x | | 4x+5(2x-5)=-5 | | -9x-15=(2x+1)+x | | -12x+43=-7x+28 | | 4x-10=2x(2-5) | | 10*40+3= | | 4=-2(x+11) | | y^2(x-9)+1(x-9)=0 | | 1.5=x/6.5 | | 6a-4=2a+76 | | -2(t-4)+8t=4t-5 | | 5x+2y=98 | | -8(a,8-2)=26 | | 3x+201=153 | | 2.2+x=-4.7 | | n-(-1.2)=-9.3 | | 6z-62z+2=0 | | 6+4n=n-11 | | 4x/x-7-3x/x-3 | | 7(s-5)=43 | | 0=5x^2-10x-4xy+8y | | .3(x+2)-0.5(x+2)=.02x-.04 | | 5x-8=7x-6 | | 6(-4+5h-5-3h)= | | 6[6-(-7x-3)]=168x+108 | | 3n^2+9x+9=3 | | 3x-0.1=0.2-0.4(7-2x) | | 2x/2=0/2 | | 13-2m=19 |